الحضانة في القانون المالديفي : دراسة فقهية تقويمية - أحمد، إبراهيم (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
In this study, the researcher has examined the child custody law in the Maldives by doing an analytical evaluative study of Islamic Jurisprudence, paving it with a glance at the history of the Maldives and Maldivian Family Law. The researcher has taken the inductive descriptive analytical method, as evidence for him in the flow of the article, and worked on the analysis to reach useful results. He used the comparative approach, whereby a comparison between the statements of the Muslim scholars and Maldivian Law was made, depending on the most authentic and prevailing views. The researcher has presented the concept of child custody its legality in Islamic Law, its legal rulings, its conditions, when it is dropped and when it is reverted in Islamic Jurisprudence. The researcher discussed both ancient and modern resources of Maldivian law, revealing its shortcomings and explaining the methods of treatment. The practical side of child custody and some of the cases considered by the Maldivian judiciary are also assesed. Then he concluded that the most important results reached were, that the aims of child custody is taking care and maintenance. The motive behind it is to fill the vacuum created by mothers being busy and child custody as children's right which includes protecting them physically, socially and spiritually so that they get a proper upbringing in all aspects.